Guys l would like to know how does the the voltage at node D become : Vd=-(Vc-Va)=Va-Vc
Apr 14, 2009 #1 Nyasha 127 0 Guys l would like to know how does the the voltage at node D become : Vd=-(Vc-Va)=Va-Vc Attachments Untitled.jpg 14 KB Views: 242
Related Engineering and Comp Sci Homework Help News on Phys.org Bacteria on the International Space Station no more dangerous than earthbound strains What if we could teach photons to behave like electrons? Veggie-loving fish could be the new white meat
Related Engineering and Comp Sci Homework Help News on Phys.org Bacteria on the International Space Station no more dangerous than earthbound strains What if we could teach photons to behave like electrons? Veggie-loving fish could be the new white meat
Apr 15, 2009 #2 The Electrician Gold Member 1,246 152 Calculate ix = (VC-VA)/2. You see why this is, I hope. Ask if you don't. Then the dependent source feeding VD has a voltage VD =-2*ix. Substituting what we calculated for ix above, we have VD = -2*ix = -2*(VC-VA)/2 = VA-VC.
Calculate ix = (VC-VA)/2. You see why this is, I hope. Ask if you don't. Then the dependent source feeding VD has a voltage VD =-2*ix. Substituting what we calculated for ix above, we have VD = -2*ix = -2*(VC-VA)/2 = VA-VC.